Digital Volunteering and Organizational Adaptability: The Roles of Conflict Management and Social Capital in Indonesia’s Humanitarian Organizations - Eka Kadharpa Utama Dewayani; Dustin Tarinque Loreño (Global Review of Tourism and Social Sciences, 2026)
The rapid advancement of digital technology has transformed how humanitarian organizations mobilize and engage volunteers. Within this shift, digital volunteering has become essential for improving coordination, transparency, and responsiveness in disaster management. This study examines the causal relationships among Digital Volunteering (DV), Conflict Management (CM), Social Capital (SC), and Resistance to Change (RC) within the Muhammadiyah Disaster Management Center (MDMC) in East Java, Indonesia. Using a quantitative explanatory design, data were collected from 200 active digital volunteers and analyzed with Partial Least Squares Structural Equation Modeling (PLS-SEM). Results show that Digital Volunteering positively affects Conflict Management and negatively influences Resistance to Change. Furthermore, Conflict Management mediates the link between DV and RC, while Social Capital moderates both DV–RC and CM–RC relationships. These findings highlight how digital engagement enhances communication and collaboration while reducing resistance through effective conflict management and strong social networks. The study contributes to understanding how digital transformation strengthens volunteer adaptability and organizational resilience in humanitarian settings